2021
DOI: 10.20527/bipf.v9i1.9319
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Science, Technology, Engineering, and Mathematics (STEM) Approaches on Critical Thinking Skills Using PBL Learning Models

Abstract: The purpose of this study was to determine the effect of Science, Technology, Engineering, and Mathematics (STEM) approach to the improvement of critical thinking skills using Problem Based Learning (PBL) models. The population of the research was all of the 10th grade IPA students in SMA Negeri 7 Bandar Lampung which were 233 students. The selection of research sample used a purposive sampling technique with the sample of class X IPA 5 that consisted of 31 students as the experimental group and the class X IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In addition, students also make their own decisions within a predetermined framework. Another study conducted by Jamaludin concluded that PjBL could significantly improve students' critical (Permana et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, students also make their own decisions within a predetermined framework. Another study conducted by Jamaludin concluded that PjBL could significantly improve students' critical (Permana et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It is evidenced by the results of students who can answer the questions and integrate their knowledge to solve problems in everyday life and relate them to the subject matter concepts. Applying STEM-PBL to questions by making them analyze everyday life problems can improve students' critical thinking skills (Hasanah et al, 2021;Setia Permana et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…STEM learning integrates science, technology, engineering, and mathematics learning which is very much needed in encouraging students' skills in the 21st century (Davidi, Sennen, & Supardi, 2021;Santoso & Mosik, 2019). In its implementation, STEM can be integrated with various learning models such as Problem Based Learning (PBL), Project Based Learning (PjBL), Discovery Learning, and Inquiry-Based Learning (Putri, Pursitasari, & Rubini, 2020;Setia Permana, Nyeneng, & Distrik, 2021). STEM integration with PBL provides opportunities for students to apply knowledge to existing problems or issues in solving problems (Farwati, Permanasari, Firman, & Suhery, 2017;Hasanah, Tenri Pada, Safrida, Artika, & Mudatsir, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The learning characteristics of the PjBL-STEM model, which focuses on the 'student-centred model', significantly influence problemsolving skills (Putri & Dwikoranto, 2022). The use of STEM approach using the PBL learning model can be used as an alternative for teachers in efforts to improve students' 21st-century skills, one of which is students' critical thinking (Permana et al, 2021) so that it should be able to influence students' collaboration skills considering that in this model group activities that the features will greatly help in e-learning are needed. This is in line with the needs analysis conducted showing 100% of students think that there is a need to implement STEM-based e-learning for physics learning, even 78.6% of students feel that using e-learning at STEM-Based Soundwave materials has the potential to improve their collaboration skills.…”
Section: Introductionmentioning
confidence: 99%